Taxonomic review of the genus Hypomicrogaster Ashmead (Hymenoptera: Braconidae: Microgastrinae), with descriptions of 40 new species - Valerio, A. A.; Whitfield, J.b. (Zootaxa, 2015)
A taxonomic review of the genus Hypomicrogaster Ashmead is presented with the redescription and redelimitation of the already named species Hypomicrogaster ecus Nixon, H. imitator (Ashmead), H. tydeus Nixon and H. zonaria (Say). The review also implies eleven new synonymies, and a new combination for the species H. areolaris (Blanchard). Also, the present revision identified 40 new Hypomicrogaster species: Hypomicrogaster aodous n. sp., H. aplebis n. sp., H. cernus n. sp., H. crocinus n. sp., H. daktulios n. sp., H. deltis n. sp., H. duo n. sp., H. epipagis n. sp., H. espera n. sp., H. evrys n. sp., H. guille n. sp., H. hektos n. sp., H. hupsos n. sp., H. ingensis n. sp., H. insolitus n. sp., H. inversalis n. sp., H. koinos n. sp., H. largus n. sp., H. laxus n. sp., H. linearis n. sp., H. lineatus n. sp., H. luisi n. sp., H. masoni n. sp., H. mesos n. sp., H. mikrosus n. sp., H. multus n. sp., H. pectinatus n. sp., H. plagios n. sp., H. pollex n. sp., H. rugosus n. sp., H. scindus n. sp., H. sicingens n. sp., H. sicpollex n. sp., H. sicscindus n. sp., H. siderion n. sp., H. spatulae n. sp., H. specialis n. sp., H. tantillus n. sp., H. tetra n. sp., H. zan n. sp. The Hypomicrogaster species are using as hosts 11 families of Lepidoptera, and 52 confirmed lepidopteran species feeding on 34 families of plants. Additionally, a fully illustrated key to all known described species of Hypomicrogaster is presented.